Effectiveness Of Epidural Steroid Injection For Pain Management In Buerger's Disease: A Non-Operative Alternative For Refractory Patients - Handra Juanda; Ramzi Asrial; Indra Jaya (Jurnal Ners, 2026)
Background: Buerger’s disease (thromboangiitis obliterans) is a non-atherosclerotic, segmental vasculitis affecting small to medium-sized arteries and veins, strongly associated with tobacco use. Chronic ischemic pain is often challenging to manage despite pharmacologic and surgical options. Epidural steroid injection (ESI), commonly used for radicular pain, may modulate inflammatory and nociceptive pathways at the spinal level and provide benefit in ischemic pain. Case Presentation: A 34-year-old male with Buerger’s disease presented with severe refractory ischemic pain of the right lower extremity. CT angiography revealed distal occlusion of the right external iliac artery, stenosis of the left superficial femoral artery, and stenosis of the left anterior tibial artery. Despite treatment with NSAIDs, tramadol, vasodilators, aspirin, and iloprost infusion, pain relief was minimal (VAS 8/10). As the patient declined operative interventions, ESI was performed as a non-operative alternative. Significant improvement was noted (VAS reduced from 8 to 3 within 1 week) with enhanced functional mobility and no complications. Conclusion:ESI may serve as an effective adjunct for refractory ischemic pain in Buerger’s disease, especially in patients who are unwilling or unsuitable for surgical intervention.